NILAI-NILAI SOSIAL DALAM CERITA RAKYAT “PANGERAN BARASA” - Andi Inayah Soraya; Nurani; Amala Rosalind Anjanette (JURNAL ILMU BUDAYA, 2022)
This study aims to analyse social values based on local wisdom in folklore entitled “Pangeran Barasa”, therefore it can be used as a role model for local community and people Indonesian in general. This study applied structuralism approach. The method used in this research is descriptive qualitative. The data collection techniques implemented reading and note-taking the dialogs, setting, and plot. Source of the primary data is “Pangeran Barasa” written by Nuraidar Agus and the secondary data were taken from other references which relevant to this research. The finding of this analysis there are some social values based on local wisdom in this folklore which categorized as love, responsibility and harmony of life. Love category includes dedication, helping each other, brotherhood, and loyalty. Responsibility includes of politeness, a sense of belonging, respect, and empathy. Last, life harmony category involves in equity and cooperation. Key Words: Social Value, Local Wisdom, Folklore